Commercially Available Prenatal Vitamins Do Not Meet American College of Obstetricians and Gynecologists Nutritional Guidelines - Cai, Fei; Young, Benjamin K.; Mccoy, Jennifer A. (American Journal of Perinatology, 2023)
Objective This study aimed to evaluate the reported amount of the American College of Obstetricians and Gynecologists (ACOG) recommended nutrients in commercially available, over-the-counter prenatal vitamins (PNVs) in the United States, to assess their adequacy compared with the ACOG guidelines, and to compare these supplements by cost.Study Design The top 30 online Amazon and Google shopping items found using “prenatal vitamins” in September 2022 were included for analysis if they included the words “prenatal” and “vitamin” in the label and contained multiple nutrients. Duplicates between Amazon and Google were excluded as well as vitamins that did not list all ingredients. The reported amounts of 11 key nutrients, as recommended by the ACOG, for each product were recorded, as well as supplemental form and cost per 30-day supply. A cost analysis was done of PNVs that met the ACOG recommendations for the highlighted nutrients compared with those that did not. Five out of the 11 key nutrients (folic acid, iron, docosahexaenoic acid, vitamin D, and calcium) were specifically highlighted, as deficiencies in these nutrients are known to correlate with significant clinical outcomes in pregnancy.Results A total of 48 unique PNVs were included for final analysis. Of these PNVs, none were compliant with suggested amounts of all five key vitamins and nutrients. No products met daily recommendations for calcium. Only five PNVs were compliant with recommendations with 4/5 key nutrients. Of note, 27% of PNVs did not have the recommended amount of folic acid (13/48). The median cost of PNVs that were not compliant with the four nutrients mentioned above was $18.99 (interquartile range [IQR]: $10.00–30.29), which was not statistically different from the median cost of the PNVs that did meet compliance with the four nutrients, which was $18.16 (IQR: $9.13–26.99), p = 0.55.Conclusion There were significant variations in the level of nutrients and cost of commercially available, over-the-counter PNVs in the United States. This raises concern that there should be more regulation of PNVs.Key Points
Keywords: prenatal care; prenatal vitamins; nutrients; iron; folic acid; pregnancy